ANALISIS DETERMINAN INVESTASI DI INDONESIA - Nunung Emalya Putri; Alpon Satrianto (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study aims to determine and analyze the extent of the influence of human development, labor, infrastructure and inflation indices on investment in Indonesia. This type of research is descriptive and associative research using a quantitative approach. The data used in this study are panel data with the 2016-2020 time series and cross sections of 34 provinces in Indonesia, which are sourced from BPS. The analytical method used is the classen typology and multinomial logistic regression. The results showed that: (1) the human development index variable had a positive and significant effect on investment in the classification of fast-developing and fast-growing and depressed areas, while it had a positive and insignificant effect on rapidly developing regions (2) the labor variable had a negative and significant effect on investment in the classification of fast-developed and fast-growing, depressed and rapidly developing regions (3) the infrastructure variable has a negative and significant effect on fast-developing and fast-growing regions, while a negative and insignificant effect on depressed and rapidly developing developed areas. (4) inflation has no significant effect on investment in the classification of fast-developed and fast-growing, depressed and fast-developing regions.